2017
DOI: 10.1016/j.jchemneu.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-specific antibodies targeting the amino terminus of the human dopamine transporter

Abstract: The dopamine transporter (DAT), which mediates the inactivation of released dopamine through its reuptake, is the primary molecular target for the actions of psychostimulants. An increasing number of studies support an essential role for phosphorylation of serines (Ser) in the distal amino (N) terminus of DAT in regulating its function. Still, the molecular details of the regulation of phosphorylation and its impact on function are not fully understood. To address this, we have developed and characterized two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Early studies demonstrating the ability of DAT to undergo phosphorylation were performed using 32 P metabolic labeling in heterologous expression systems (Granas, Ferrer, Loland, Javitch, & Gether, 2003; Huff, Vaughan, Kuhar, & Uhl, 1997) as well as in rat and mouse striatal tissue (Foster, Pananusorn, & Vaughan, 2002; Vaughan, Huff, Uhl, & Kuhar, 1997). More recently, our group developed phosphospecific anti-DAT antibodies to probe the phosphorylation of individual serine resides in DAT in response to various stimuli (Karam, Sen, & Javitch, 2017). These studies showed that DAT phosphorylation is rapidly elevated by activation of protein kinase C (PKC) with phorbol 12-myristate, 13-acetate (PMA) (Huff et al, 1997; Karam et al, 2017; Vaughan et al, 1997), diacylglycerol analogs (Vaughan et al, 1997), or G q activation by G protein-coupled receptor agonists (Granas et al, 2003).…”
Section: A Role For Dat N-terminal Phosphorylation In Dat-mediated Damentioning
confidence: 99%
See 4 more Smart Citations
“…Early studies demonstrating the ability of DAT to undergo phosphorylation were performed using 32 P metabolic labeling in heterologous expression systems (Granas, Ferrer, Loland, Javitch, & Gether, 2003; Huff, Vaughan, Kuhar, & Uhl, 1997) as well as in rat and mouse striatal tissue (Foster, Pananusorn, & Vaughan, 2002; Vaughan, Huff, Uhl, & Kuhar, 1997). More recently, our group developed phosphospecific anti-DAT antibodies to probe the phosphorylation of individual serine resides in DAT in response to various stimuli (Karam, Sen, & Javitch, 2017). These studies showed that DAT phosphorylation is rapidly elevated by activation of protein kinase C (PKC) with phorbol 12-myristate, 13-acetate (PMA) (Huff et al, 1997; Karam et al, 2017; Vaughan et al, 1997), diacylglycerol analogs (Vaughan et al, 1997), or G q activation by G protein-coupled receptor agonists (Granas et al, 2003).…”
Section: A Role For Dat N-terminal Phosphorylation In Dat-mediated Damentioning
confidence: 99%
“…More recently, our group developed phosphospecific anti-DAT antibodies to probe the phosphorylation of individual serine resides in DAT in response to various stimuli (Karam, Sen, & Javitch, 2017). These studies showed that DAT phosphorylation is rapidly elevated by activation of protein kinase C (PKC) with phorbol 12-myristate, 13-acetate (PMA) (Huff et al, 1997; Karam et al, 2017; Vaughan et al, 1997), diacylglycerol analogs (Vaughan et al, 1997), or G q activation by G protein-coupled receptor agonists (Granas et al, 2003). DAT phosphorylation was also shown to be strongly enhanced by treating cells with protein phosphatase inhibitors such as okadaic acid (OA), indicating that the transporter is subject to ongoing kinase activity even in the absence of exogenous kinase activators (Foster, Pananusorn, Cervinski, Holden, & Vaughan, 2003; Foster et al, 2002; Huff et al, 1997; Karam et al, 2017; Vaughan et al, 1997).…”
Section: A Role For Dat N-terminal Phosphorylation In Dat-mediated Damentioning
confidence: 99%
See 3 more Smart Citations